New onset diabetes presenting with DKA, spontaneous pneumomediastinum and subcutaneous emphysema: a case series. (7th October 2020) - Sharma, Aditi; Khan, Shaila; Chicco, Maria; Peters, Christopher; Oliver, Nicholas; Reddy, Monika
Abstract: Hamman's syndrome, first described by Dr Louis Hamman in 1939, is a syndrome of spontaneous pneumomediastinum and subcutaneous emphysema. It is a rare complication of diabetic ketoacidosis (DKA), and self‐resolves within days with conservative management. Limited awareness about this condition may lead to an initial misdiagnosis of secondary pneumomediastinum due to spontaneous oesophageal perforation (Boerhaave's syndrome), which is associated with high mortality and often requires invasive management. It is important to distinguish between the two conditions to avoid unnecessary investigations, procedures and delays to hospital discharge. We hereby present our experience, between the years 2017–2019, of managing three cases of Hamman's syndrome, in young men aged 18–22 years, with no previous history of diabetes, presenting with severe vomiting, osmotic symptoms and a diagnosis of DKA. In all three cases the admission chest radiograph showed pneumomediastinum and in two of the cases surgical emphysema was also noted. The presentation with vomiting in association with the chest X‐ray findings raised a high index of suspicion for spontaneous oesophageal perforation. Consequently, they were kept nil‐by‐mouth for several days and cared for in high dependency settings. Total parenteral nutrition was initiated in two cases. Each individual underwent computer tomography of the chest, and sequential water‐soluble oral contrast swallow tests with no evidence of an oesophageal defect. The individuals were conservatively managed and discharged following a length of stay ranging from five to 14 days. Copyright © 2020 John Wiley & Sons.